The Synthesis Of Non-Stoichiometric Cordierite Via Glass Ceramic Route Using Calcined Talc And Kaolin - Johar, Banjuraizah (2011)
Various non-stoichiometric cordierite compositions were synthesized via glass route. Densification and crystallization behavior of the glass were determined by dilatometry and differential thermal analysis, while phase transformation of glass to glass-ceramic by X-ray diffraction. CTE, dielectric properties, density and porosity percentages as well as the microstructure of glass-ceramic were carried out to correlate its variation with the compositions. 100 wt% α-cordierite phase with the density 2.54 g/cm3, porosity 0.4% has succesfully being obtained at lower heat treatment temperature of 900oC for 2 hours using non-stoichiometric cordierite compositions synthesized from mainly calcined talc and kaolin as initial raw materials.